The impact of social norms on health‐related belief update. Issue 2 (13th October 2021) - Vlasceanu, Madalina; Coman, Alin
Abstract: People are constantly bombarded with information they could use to adjust their beliefs. Here, we are interested in exploring the impact of social norms on health‐related belief update. To investigate, we recruited a sample of 200 Princeton University students, who first rated the accuracy of a set of health statements (pre‐test). They were then provided with relevant evidence either in favor or against the initial statements, and were asked to rate how convincing each piece of evidence was. The evidence was randomly assigned to appear as normative or non‐normative, and anecdotal or scientific. Finally, participants rated the accuracy of the initial set of statements again (post‐test). The results show that participants rationally updated their beliefs more when the evidence was scientific compared to when it was anecdotal. More importantly to our primary inquiry, the results show that participants changed their beliefs more in line with the evidence when the evidence was portrayed as normative compared to when the evidence was portrayed as non‐normative, pointing to the impactful influence social norms have on health beliefs. Both effects were mediated by participants' subjective evaluation of the convincingness of the evidence, indicating the mechanism by which evidence is selectively incorporated into belief systems.